Metaphylaxis - Siener, Roswitha (Journal of Pediatric Biochemistry, 2014)
Effective metaphylactic treatment is available for the different types of stone. A high urine volume achieved by sufficient intake of appropriate beverages is the most important goal in the treatment of the pediatric stone patient. Specific dietary and, if required, pharmacological measures tailored to the individual requirements can prevent or reduce recurrences and decrease the burden of invasive procedures in patients with recurrent stone disease.
Keywords: Urinary stone disease; pediatric patient; children; dietary measures; fluid intake; pharmacological treatment